Professional practice José María Roy School - Pacheco R., Liz A. (David, Panamá : UDELAS, 2010)
In this professional practice report, I going to talk about the elementary School José María Roy.
INDEX INTRODUCTION CHAPTER I Referential and institutional frame CAPTER II Descrition of the professional practice 2.1. Definition and characteristics of the professional practice 2.1.1. Selection if criteraia 2.1.2. Relations the thematuc with the especialty 2.2. Programs relatead with the professional practice 2.3. Objective of the professional practice 2.4. Population beneficiary 2.4.1. Direct 2.4.. Indirect 2.5. Develop activities during the professional practice 2.5.1. Diagnosis 2.5.2. Intervention 2.5.3. Result 2.6. Resources 2.7. Chronogram CHAPTER III Result of the professional practice CONCLUSION RELEVANT CONSIDERATION RECOMENDATION REFERENCES ATTACHMENTS
Incluye Index
Documento presentado para optar por el título de Licenciatura en Docencia en Ingles
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- INFORME DE PRÁCTICA DE LICENCIATURA -- TEACHING; FACULTAD ESPECIAL DE EDUCACIÓN; LICENCIATURA EN DOCENCIA EN INGLÉS; JOSÉ MARÍA ROY SCHOOL